2014
DOI: 10.1038/srep03822
|View full text |Cite
|
Sign up to set email alerts
|

Prostatic ischemia induces ventral prostatic hyperplasia in the SHR; possible mechanism of development of BPH

Abstract: In the light of increasing evidence that benign prostatic hyperplasia is associated with cardiovascular disease, we have investigated the relationship between prostatic blood flow and prostatic hyperplasia in the spontaneously-hypertensive-rat (SHR). Twelve-week-old male SHRs were treated with nicorandil for six weeks. Wistar-Kyoto rats were used as controls. Six weeks after nicorandil treatment, blood pressure and the prostatic blood flow were estimated, and tissue levels of malondialdehyde, HIF-1α, TGF-β1, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
75
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(81 citation statements)
references
References 41 publications
5
75
1
Order By: Relevance
“…Moreover, it has been reported that SHR exhibit a lower basal bladder perfusion than normotensive Wistar Kyoto rats, a frequently used control strain in SHR studies; treatment of SHR with doxazosin increased perfusion and expression of NO synthase (which chronically may facilitate perfusion), whereas treatment with nifedipine did not (Yono et al 2007). The study also showed reduced prostate perfusion in SHR, a finding confirmed in a separate study (Saito et al 2014). In the latter study, treatment with nicorandil restored prostate perfusion and concomitantly reduced the elevated expression of hypoxia-inducible factor 1α, transforming growth factor β1, and basic fibroblast growth factor.…”
Section: Clinical Associations Between Atherosclerosis Risk Factors Amentioning
confidence: 55%
See 1 more Smart Citation
“…Moreover, it has been reported that SHR exhibit a lower basal bladder perfusion than normotensive Wistar Kyoto rats, a frequently used control strain in SHR studies; treatment of SHR with doxazosin increased perfusion and expression of NO synthase (which chronically may facilitate perfusion), whereas treatment with nifedipine did not (Yono et al 2007). The study also showed reduced prostate perfusion in SHR, a finding confirmed in a separate study (Saito et al 2014). In the latter study, treatment with nicorandil restored prostate perfusion and concomitantly reduced the elevated expression of hypoxia-inducible factor 1α, transforming growth factor β1, and basic fibroblast growth factor.…”
Section: Clinical Associations Between Atherosclerosis Risk Factors Amentioning
confidence: 55%
“…The rho-kinase inhibitor Y 27,632 is a known vasodilator, at least in hypertensive animals, and along with a reduction of systemic blood pressure reduced detrusor overactivity in spontaneously hypertensive rats (Rajasekaran et al 2005); however, this may reflect direct effects of rho-kinase inhibition on detrusor smooth muscle function (Peters et al 2006). Possibly more interesting are findings with nicorandil, which reduced prostate weight and increased prostate perfusion in SHR in the absence of effects on systemic blood pressure (Saito et al 2014). Limited clinical data show that a combination of the α 1 -adrenoceptor antagonist terazosin and the Ca 2+ -entry blocker amlodipine yielded superior blood pressure and LUTS reduction than either monotherapy in a group of 355 men (Liu et al 2009).…”
Section: Effects Of Therapeutics On Bladder Perfusionmentioning
confidence: 94%
“…In the atherosclerosis-induced chronic bladder ischemia rat model, the resulting detrusor overactivity leads to an increase in the voiding frequency (18). Since atherosclerosis is thought to be a risk factor for benign prostatic hyperplasia (BPH), it has been suggested that there is a relationship between high vascular resistance and the development of BPH (12,23). Therefore, it is thought that the hypertension and/or arteriosclerosis that reduces arterial blood flow and subsequently causes ischemia will induce BPH or overactive bladder.…”
mentioning
confidence: 99%
“…Rats were anesthetized with urethane (0.6 g/kg subcutaneously) and placed in a restraining cage (NAIGAI-CFK-1P; NMS, Tokyo, Japan), after which a polyethylene catheter (PE50; Clay Adams, NJ, USA) was inserted transurethrally into the bladder. This catheter was then connected to an infua lower prostate blood flow and have an increased prostate size (23). In the atherosclerosis-induced chronic bladder ischemia rat model, the resulting detrusor overactivity leads to an increase in the voiding frequency (18).…”
mentioning
confidence: 99%
“…In the last decade, the pathogenesis of BPH began to consider from the perspective of vascular dysfunction, for instance, age might activate systemic vascular risk factors, resulting in disturbed blood flow (7) , furthermore, development of prostatic hyperplasia may be associated with prostatic hypoxia (8) , and with a correlation between pelvic ischemia and lower urinary tract symptoms in elderly men (9) , and also increasing the pressure in the prostate (10) . Dr. Allen's research on the Origin of Diseases identifies the causal root of prostate enlargement, namely capillary expansion.…”
Section: Introductionmentioning
confidence: 99%